Estratégias para a preservação e conservação de acervos pessoais - Alves, Danielle (2021)
The strategies directed to document preservation aim to guide the set of actions that must be applied to the collection according to its specificities, in order to prolong the durability of the media and the information they carry. In this path, the adoption of measures against accelerated deterioration and the fight against damaging agents are of extreme importance. In this context, this article was developed with the aim of disclosing strategies for the preservation and conservation of personal collections, in order to enable the subjects' autonomy in the development of techniques and in the choice of materials that can help in the safeguarding of their documents.